Improving Student's Reasoning Ability Through The Tahfizh Al-Qur’an Program - Sri Chalida; Syafruddin Syafruddin; Nandi Pinto; Muhammad Irhash Fakhruddin (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Teaching tahfizh al-Quran is one way to build student competence to do reasoning in and memorizing the Al-Qur’an. Given the changes in vision and mission as stated in the competency-based curriculum, it is necessary to make concrete efforts to prepare and make its implementation successful. This study aims to identify the teaching method of tahfizh al-Quran at the Tafsir Hadis Major, to explain the strategy of optimally developing tahfizh al-Qur'an so that it can improve students' reasoning abilities and identify the level of students' reasoning ability after participating in the tahfizh al-Qur'an program at the Tafsir Hadis Major. This study is a development activity carried out in collaboration between students and lecturers to conceptually design the design of teaching materials based on experience and existing conditions. These two stages will always be accompanied by a process of evaluation and reflection to improve the designs developed. This research shows that first; the sima'i method is a method that is widely used by students in memorizing the Qur'an, secondly; the strategy of fostering tahfizh al-Quran should be done with the muraja'ah method, Third; From the results of the calculation of the student's reasoning ability test scores, the average score of students' reasoning abilities in the high category was 48.82, the average category was 41.06, and the low category has obtained an average of 39. These different average gains indicate that the levels of students' reasoning abilities are different.